DC Fault Ride-Through Strategy Based on Overmodulation. Issue 1 (March 2021) - Cui, M; Li, K J; Liu, Z J; Li, L Z
Abstract: The hybrid modular multilevel converter (hybrid MMC) can realize DC fault ride-through based on the capability of overmodulation and can continue to output reactive power to AC side during the fault, which can speed up the recovery of DC grid power after the fault is cleared. This paper improves the control strategy of DC fault ride-through. During the bipolar short circuit on the DC side, hybrid MMC blocks the short-circuit current of the DC side by adjusting the reference value of DC voltage dynamically. Moreover, the average value of the sub-modules is introduced into the active current controller to maintain the balance of the sub-module voltage. Then, the performance of the improved strategy is verified by MATLAB/Simulink simulation model.